1988
DOI: 10.1002/j.1556-6978.1988.tb00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Verbal and Vocal Cues of Counselor Self‐Confidence on Clients' Perceptions

Abstract: The authors found that vocal-but not verbal-cues of counselor self-confidence were related to client perceptions of expertness, attractiveness, trustworthiness, and associated satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It is also possible that children in Experiment 1 might have a better, or earlier, understanding of justified hesitancy than their learning preferences suggest, but find it difficult to overcome a more general bias to avoid information from hesitant individuals. Even adults are biased to avoid hesitant individuals [e.g., [21][22][23] and in our design children would have to overcome any hesitancy avoidance to favor the well-calibrated model. To address these limitations in Experiment 1, Experiments 2 and 3 equated the models' level of confidence during the History Phase (both confident or both hesitant) and varied which of the models was informed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that children in Experiment 1 might have a better, or earlier, understanding of justified hesitancy than their learning preferences suggest, but find it difficult to overcome a more general bias to avoid information from hesitant individuals. Even adults are biased to avoid hesitant individuals [e.g., [21][22][23] and in our design children would have to overcome any hesitancy avoidance to favor the well-calibrated model. To address these limitations in Experiment 1, Experiments 2 and 3 equated the models' level of confidence during the History Phase (both confident or both hesitant) and varied which of the models was informed.…”
Section: Discussionmentioning
confidence: 99%
“…The Confidence Heuristic Model maintains that people make rapid judgments of credibility, such as how accurate the information is or how trustworthy an individual is, based on the confidence expressed in the message or by the messenger. The confidence heuristic has been the focus of considerable attention in legal settings, political decision-making, clinical settings, and consumer economics [e.g., [21][22][23][24][25]. For example, adults tend to vote for more confident political candidates [26,27], and are more trusting of testimony from confident witnesses in mock jury trials [28,29].…”
Section: Confidence Is Good But Overconfidence Always Sinks the Shipmentioning
confidence: 99%
“…Of considerable interest is what level and style of charismatic behavior may be optimal. Although simply increasing the amplitude of therapist nonverbal behavior can make it more persuasive (Packwood, 1974), a major differentiation may be between low and medium levels, with higher levels not always necessary (Barak et al, 1988). Other evidence suggests that length of speaking time, fluency of speech, and speech rate are related to credibility and influence (Burgoon, Dunbar, & Segrin, 2002; Pentland, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To select cues, we drew on conceptual definitions of self‐esteem (Baumeister et al, ; Zeigler‐Hill et al, ), measures of behavioral observation of self‐esteem (e.g., Demo, ; Helmreich & Stapp, ; Metcalfe, ; Savin‐Williams & Jaquish, ), empirical findings linking self‐esteem to specific cues (e.g., Barak et al, ; Berry, ; Langlois et al, ; Naumann et al, ), and cues typically expressed and perceived in zero‐acquaintance situations (e.g., Back, Schmukle, & Egloff, ; Borkenau & Liebler, ). In sum, we selected over 80 cues of physical appearance, nonverbal behavior, vocal, and verbal aspects of perceivable information theoretically and empirically deemed relevant to self‐esteem.…”
Section: Methodsmentioning
confidence: 99%
“…Wood & Forest, , p. 264). Further, vocal aspects (e.g., higher voice tones and a relatively loud, powerful, unhesitant voice) and verbal aspects (e.g., self‐assured content) might be indicative of people's higher self‐esteem and might be utilized by observers to form judgments of individuals’ self‐confidence (Barak, Shapira, & Fisher, ; McAleer, Todorov, & Belin, ; Scherer, ). Naumann et al () identified cues that were observable in spontaneously posed photographs that were associated with targets’ self‐informant composite of self‐esteem and observers’ judgments of targets’ self‐esteem.…”
Section: The Present Researchmentioning
confidence: 99%